Clomiphene citrate in infertile women with ovulatory dysfunction - Jefferson Cortéz, Luz (2015)
Retrospective study in Infertility Clinic Loayza Hospital in Lima, between January 1980 and December 1991. They include 56 infertile ovulatory dysfunction treated with clomiphene citrate for a total of 197 cycles. Thirty patients had chronic anovulation or oligo-ovulation, and 26 patients with luteal phase defect, in 83% of the first group of patients it was possible to induce ovulation, pregnancy rate being 29%. Most patients studied had peritoneal tubi factor associated with ovulatory dysfunction, factor associated with a poor prognosis for pregnancy (p <0.001). In 69% of pregnancies, these were achieved during the first three months of treatment, the required dose being 50 to 100 mg / day in 94% of cases. There were no multiple pregnancies and 1.6% of patients presented clinical data cycles of mild ovarian hyperstimulation.